Programmed cell death-related prognostic genes mediate dysregulation of the immune microenvironment in triple-negative breast cancer - Ma, Xiaowen; Shan, Hui; Chen, Zhao; Shao, Rongzi; Han, Ning (Frontiers in Immunology, 2025)
BackgroundProgrammed Cell death (PCD) encompasses a spectrum of genetically regulated cell death processes and plays a double-edged sword role in neoplastic progression and therapeutic resistance of Triple-Negative Breast Cancer(TNBC)through the tumor microenvironment (TME). However, the specific mechanisms by which PCD mediates microenvironmental dysregulation remain elusive.MethodsAnalyzing nine samples of TNBC through single-cell RNA sequencing (scRNA-seq), this study employed nonnegative matrix factorization (NMF) to assess genes associated with 13 PCD modes. Single-cell regulatory network inference and clustering (SCENIC), Monocle, CellChat, and scMetabolism were used for pseudotime analysis, intercellular communication mapping, determination of transcription factor activities (TFs), and immune infiltration of PCD-related cell clusters in TME. A robust prognostic model and drug resistance analysis were constructed using gene set enrichment analysis (GSEA), Kaplan-Meier survival analysis, and multivariable Cox regression. Finally, hub genes and critical PCD-related cell clusters were validated in the clinical breast cancer samples and the TNBC model mice.ResultsThis investigation demonstrated that PCD significantly modulated the functional and phenotypic diversity of fibroblasts, macrophages, T cells, and B cells in the TME of TNBC. Furthermore, this study revealed that PCD-regulated CEBPB-positive cancer-associated fibroblast (CAF) populations are a key determinant of the TNBC immune Microenvironment heterogeneity and poor prognosis. Notably, CellChat analysis unveiled diverse and extensive interactions between PCD-related cell clusters and tumor immune cells, highlighting the CEBPB+ CAF subtype as a signaling ligand communicated with other immune cell clusters through the Midkine (MDK)-Nucleolin (NCL) signaling axis. Moreover, the TIDE analysis verified that CEBPB+ CAF is a predictor of poor prognosis in Immunotherapy. The ex vivo analyses of tumor specimens from both TNBC patients and syngeneic murine models were performed by quantitative reverse-transcription PCR (qRT-PCR), immunoblotting, immunohistochemical staining, and multiplexed immunofluorescence co-localization assays. They confirmed differential expression of the PCD-related prognostic genes and the presence of CEBPB+ CAFs.ConclusionIn summary, our study provides a comprehensive molecular framework to understand the role of PCD-mediated TME dysregulation in TNBC pathogenesis. This study also offers new insights into the underlying mechanisms of immune therapy resistance in TNBC and identifies promising therapeutic targets for enhancing treatment efficacy and patient outcomes.